Improved method for the catheterization of the right ventricle in a rat model of pulmonary artery hypertension. (21st January 2020) - Tontodonati, Marcello; Ridley, Debbie; Remie, René; Clements, Peter
Abstract: Ventricle catheterization in the rat is widely practiced in cardiopulmonary research. The catheters deployed are either fluid filled or solid tip pressure or pressure–volume catheters. The access to the right ventricle is through the right jugular vein, most commonly without direct visualization such as fluoroscopy. Advancement of the catheter tip is aided by visualizing the pressure signals of the monitoring/recording systems used. This approach may present challenges due to various reasons, including the stiffness of new catheters, their dimensions or anatomical changes associated with the animal disease model. In this article, we present a novel approach, which has been optimized, successfully validated surgically and adopted in current projects. It has been shown to improve both the overall quality of the signals recorded and the time to access the right ventricle, thus reducing the overall time of surgery. The method presented in this article is safe, easy to reproduce and does not require additional skills compared to a more 'standard' approach.